Changer de sexe: identités transsexuelles - Augst-Merelle, Alexandra; Nicot, Stéphanie (Cavalier bleu, 2006)
Rédigé par deux transgenres, un portrait de la communauté transexuelle française qui fait justice des préjugés et s'efforce de balayer toutes les idées reçues.
Section: 187, [4] pages ; 23 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; europe; france; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; militance; premier cycle; périodes historiques; queer; queer of color; régions géographiques; shm4000; systèmes d'oppressions; thématiques; transféminisme

The dynamics of emotion and activism: Grief, gender, and collective identity in revolutionary nicaragua - de Volo, Lorraine (Mobilization: An International Quarterly, 2006)
This article argues for a multidirectional and gendered understanding of the causal relationship between emotion and collective identity. Based on interviews and participant observation with core members of a Nicaraguan mothers' organization, I identify four ways in which emotion and identity are causally linked: emotion-based identity, therapy, affective bonds, and change in collective identity leading to change in grieving style. These indicate a dynamic relationship between emotion and collective identity. Furthermore, to understand emotion-based collective identity and perceptions of the emotional benefits of participation, this relationship must be understood through gendered cultural expectations about emotion.
Keywords: 1900-1999; 1990-1999; amériques; genre; militance; mouvements sociaux; nicaragua; périodes historiques; ressource en ligne; régions géographiques; thématiques; émotions; étude qualitative

Hygiène et modernisation - Ross, Kristin (Rouler plus vite, laver plus blanc : modernisation de la France et décolonisation au tournant des années 60, 2006)
Keywords: 1900-1999; 1950-1959; changement social; cours; discipline; europe; fem1000; france; histoire; militance; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques

Radical gestures: feminism and performance art in North America - Wark, Jayne (McGill-Queen's University Press, 2006)
Wark brings together a wide range of artists, including Lisa Steele, Martha Rosler, Lynda Benglis, Gillian Collyer, Margaret Dragu, and Sylvie Tourangeau, and provides detailed readings and viewings of individual pieces, many of which have not been studied in detail before. She reassesses assumptions about the generational and thematic characteristics of feminist art, placing feminist performance within the wider context of minimalism, conceptualism, land art, and happenings
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; art contemporain; art féministe; arts; corps; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; militance; performance; premier cycle; périodes historiques; régions géographiques; thématiques